2011
DOI: 10.1128/mcb.01227-10
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in Ribosomal Protein Synthesis Is Sufficient To Explain Major Effects on Ribosome Production after Short-Term TOR Inactivation in Saccharomyces cerevisiae

Abstract: Ribosome synthesis depends on nutrient availability, sensed by the target of rapamycin (TOR) signaling pathway in eukaryotes. TOR inactivation affects ribosome biogenesis at the level of rRNA gene transcription, expression of ribosomal proteins (r-proteins) and biogenesis factors, preribosome processing, and transport. Here, we demonstrate that upon TOR inactivation, levels of newly synthesized ribosomal subunits drop drastically before the integrity of the RNA polymerase I apparatus is severely impaired but i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
38
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 90 publications
(139 reference statements)
6
38
1
Order By: Relevance
“…The data obtained in this study suggest that inactivation of TOR not only stops the synthesis of new ribosomes, as previous studies have demonstrated (26,45,46), but also triggers extensive turnover of the existing ribosomes, resulting in a dramatic reduction of the cellular ribosome content. mediates accumulate after depletion of the core exosome subunit Rrp41 or the core-associated nuclease Dis3.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…The data obtained in this study suggest that inactivation of TOR not only stops the synthesis of new ribosomes, as previous studies have demonstrated (26,45,46), but also triggers extensive turnover of the existing ribosomes, resulting in a dramatic reduction of the cellular ribosome content. mediates accumulate after depletion of the core exosome subunit Rrp41 or the core-associated nuclease Dis3.…”
Section: Discussionsupporting
confidence: 77%
“…Previous studies found that the synthesis of new ribosomes stops within minutes after treatment of yeast cells with rapamycin (45,46). To investigate the fate of ribosomes remaining in cells after TOR inactivation, we performed quantitative assays to examine the rRNA contents in the common laboratory S. cerevisiae strain W303 before and after rapamycin treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Processing of the 35S pre-rRNA occurs cotranscriptionally and is dependent on the presence of ribosomal proteins (Tschochner and Hurt 2003). The fast drop in RNA Pol I-dependent transcripts observed upon rapamycin treatment is apparently due to decreased translation (described above) of ribosomal proteins (Reiter et al 2011). The majority of mRNAs being translated in a rapidly growing cell encode ribosomal proteins (Warner 1999), and thus a drop in translation will rapidly reduce the levels of free ribosomal proteins that are themselves needed stoichiometrically for processing of rRNA into pre-ribosome particles.…”
Section: Tor Complexmentioning
confidence: 99%
“…mTORC1 positively regulates many anabolic processes, with the role of mTORC1 signaling in translational initiation being the best understood. More recently a function of mTOR signaling in ribosome biogenesis has also been proposed (8)(9)(10)(11)(12). In particular, mTOR has been implicated in the control of RNA polymerase I transcription and rRNA processing.…”
mentioning
confidence: 99%